Properdin Levels in Human Sepsis - Stover, Cordula M.; McDonald, John; Byrne, Simon; Lambert, David G.; Thompson, Jonathan P. (Frontiers in Immunology, 2015)
Properdin is a normal serum protein which increases the production of complement activation products by binding to C3b integral to convertase complexes and amplifying their activity at the site of activation. Thereby, it can aid in the resolution of infection but also contribute to tissue damage. In human sepsis, circulating complement C3 concentrations are decreased, though C3 is described as a positive acute phase reactant. However, properdin levels in human sepsis have not been reported. In this study, serum from 81 critically ill patients (predominately abdominal and respiratory sepsis) were analysed for properdin levels at defined points of their stay in the Intensive Care Unit (ICU) and compared with 61 age and sex-matched healthy volunteers. Properdin concentrations were significantly decreased in patients with sepsis on admission to ICU, but increased after clinical recovery to exceed levels observed in healthy volunteers. Properdin concentrations at ICU admission were decreased in non-survivors of sepsis compared to survivors, but this did not correlate with APACHE II score. However, pathologically low properdin levels (<7 microg/ml) were related to increased duration of treatment.